SWOT-Based Strategic Development for Enhancing MSMEs Digital Marketing Performance in Banda Aceh - Meutia Fadilla; Hazful Maizi; Friesca Erwan (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2026)
This study identifies the internal and external factors influencing the digital marketing performance of Micro, Small, and Medium Enterprises (MSMEs) in Banda Aceh to formulate a context-based strategic roadmap for improving digital competitiveness. The research addresses a gap left by previous studies, which focused primarily on individual platform use and sales outcomes, overlooking digital capability management as an applied information systems issue. Using a descriptive qualitative approach, the study involved 9 MSME owners from the culinary, fashion, and service sectors, selected through purposive sampling. Data were collected through semi-structured interviews, digital content observations, marketplace platforms, and document reviews. The analysis used thematic coding consisting of open, axial, and selective coding, with results mapped into a SWOT matrix. Findings indicate that the primary strengths lie in cultural storytelling, adaptability to trends, and customer loyalty. At the same time, the weaknesses include unstructured content management, weak visual branding, limited understanding of analytics, and low cybersecurity awareness. Externally, opportunities arise from government training and digital payment adoption, whereas threats include algorithmic changes and account security risks. The study contributes by repositioning digital marketing as a digital capability management problem and providing strategic guidance for MSME owners, local governments, and supporting institutions to foster sustainable digital transformation in regional contexts.